New Headway English Course : Upper-Intermediate : Workbook - Soars, Liz : Soars, John, 1951- and Devoy, Jo (Oxford, New York Oxford University Press, 1999)
New Headway Upper-Intermediate recognizes that learners at this level require a different approach to language learning. It moves away from examining language items in isolation, exploring grammatical areas in greater depth so that students begin to perceive the systems that underlie the language
Include Illustration
Keywords: English language -- English language--Pronunciation -- English language--Remedial teaching